Exploring 4-(3-carboxyphenyl)picolinic acid as a semirigid building block for the hydrothermal self-assembly of diverse metal–organic and supramolecular networks. Issue 1 (1st December 2016) - Gu, Jin-Zhong; Liang, Xiao-Xiao; Cui, Yan-Hui; Wu, Jiang; Kirillov, Alexander M.
Abstract : This contribution reports the synthesis, structural and topological features, and luminescence or magnetic properties of 11 new coordination compounds derived from an unexplored carboxylic acid block. Abstract : 4-(3-Carboxyphenyl)picolinic acid (H2 cppa) was applied as a new and virtually unexplored building block for the synthesis of eleven new coordination compounds, namely [M(Hcppa)2 (H2 O)2 ]·2H2 O M = Ni (1 ) and Zn (2 ), [M(μ3 -cppa)(H2 O)2 ] n M = Ni (3 ) and Co (4 ), [Co(μ-cppa)(2, 2′-bipy)(H2 O)]·H2 O n (5 ), [Zn(μ-cppa)(2, 2′-bipy)] n (6 ), [M(μ-cppa)(phen)(H2 O)] n M = Co (7 ), Zn (8 ), Mn (9 ), and Cu (10 ), and [Cd3 (μ3 -cppa)3 (phen)2 ]·4H2 O n (11 ). All these compounds were generated by a hydrothermal self-assembly method using the corresponding metal(ii ) chlorides, H2 cppa, and two types of N-donor ancillary ligands, selected from 2, 2′-bipyridine (2, 2′-bipy) or 1, 10-phenanthroline (phen). The obtained products1–11 were characterized by standard methods, including IR spectroscopy, elemental and thermogravimetric analyses, and powder and single-crystal X-ray diffraction. They represent the first structurally characterized compounds derived from H2 cppa. The structures of1–11 vary from a complex 3D metal–organic framework (MOF)11 to 2D coordination polymers3 and4, 1D coordination polymers5–10, and discrete 0D monomers1 and2 . Such a structural diversity is guided by the nature of the metal(ii ) node, level of deprotonation of 4-(3-carboxyphenyl)picolinic acid, and type of applied ancillary ligand. In addition, the structures of1, 2, 5, and7–10 are further extended [0D → 3D (1 and2 ), 1D → 2D (5 ), and 1D → 3D (7–10 )] into various H-bonded supramolecular networks. Both the supramolecular (in1, 2, 5, and7–10 ) and metal–organic (in3, 4, 6, and11 ) underlying networks were analyzed and classified from the topological viewpoint, revealing the distinctpcu (in1 and2 ), fes (in3 and4 ), gek1 (in5 ), 2C1 (in6 ), andsrs (in7–10 ) topological nets, whereas a topologically unique framework was identified in MOF11 . The magnetic behavior of3–5, 7, 9, and10 and luminescence properties of2, 6, 8, and11 were also investigated and discussed.